Educational technologies developed for the care of children with gastrostomy: An integrative review - Borges, Lenine Almeida Firmino; dos Santos, Maria Solange Nogueira; dos Santos, Vanusa Maria Gomes Napoleão; Chaves, Edna Maria Camelo; Rodrigues, Lidiane do Nascimento (Seven Editora, 2024)
Introduction: The educational technologies developed for the care of children with gastrostomy can help guide current educational and care practices. Objective: To identify the available evidence on the educational technologies developed for the care of children with gastrostomy. Method: This is an integrative review that considered the search in the following databases: Latin American and Caribbean Literature on Health Sciences, Online System for Search and Analysis of Medical Literature, Nursing Database and Google Scholar. Results: The technologies found were of the light-hard type, including booklets, standard operating procedures, educational manuals and videos. Conclusion: The available technologies are used by nursing, playing a fundamental role in the health education of caregivers of children with gastrostomy, especially in relation to complications and handling of the tube for feeding, cleaning and bathing. DOI:https://doi.org/10.56238/sevened2024.018-021